Pre-university students' strategies in revising ESL writing using teacher's written corrective feedback / Khairil Azwar Razali - Razali, Khairil Azwar (2014)
In Flower-Hayes (1981) Cognitive Process Theory of Writing reviewing stage, writers would evaluate and make revision to the essays. Hyland (1998) outlined four strategies used by student in revising their essays, i.e. closely follow, initial stimulus, avoidance by deletion and not related. The objectives of this study are to find out the most common strategy used by the students, and further to determine which strategy is considered as successful. A qualitative approach has been used in this study where data are collected from the analysis of students' opinion-based essays and retrospective interviews. From the study, the most common strategy used is closely follow because students believe that they need to make sure the revised essays are error-free. The result also shows that the same strategy is considered as successful as many of the revised WCF are error-free. The results implies that even though students may successfully revise the essay, they may not necessarily understand the nature of the errors committed. It is recommended that teachers provide written corrective feedback with oral feedback and this should be done while students are writing the essay, in line with Flower-Hayes Cognitive Process Theory of Writing.